(9+7)7=(6x+8x)8x

Simple and best practice solution for (9+7)7=(6x+8x)8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (9+7)7=(6x+8x)8x equation:


Simplifying
(9 + 7) * 7 = (6x + 8x) * 8x

Combine like terms: 9 + 7 = 16
(16) * 7 = (6x + 8x) * 8x

Multiply 16 * 7
112 = (6x + 8x) * 8x

Combine like terms: 6x + 8x = 14x
112 = (14x) * 8x

Remove parenthesis around (14x)
112 = 14x * 8x

Reorder the terms for easier multiplication:
112 = 14 * 8x * x

Multiply 14 * 8
112 = 112x * x

Multiply x * x
112 = 112x2

Solving
112 = 112x2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-112x2' to each side of the equation.
112 + -112x2 = 112x2 + -112x2

Combine like terms: 112x2 + -112x2 = 0
112 + -112x2 = 0

Add '-112' to each side of the equation.
112 + -112 + -112x2 = 0 + -112

Combine like terms: 112 + -112 = 0
0 + -112x2 = 0 + -112
-112x2 = 0 + -112

Combine like terms: 0 + -112 = -112
-112x2 = -112

Divide each side by '-112'.
x2 = 1

Simplifying
x2 = 1

Take the square root of each side:
x = {-1, 1}

See similar equations:

| -4x+5-3=7-3 | | 8-2t=34 | | 9j-5j=20 | | -1.75t^2+18.5t-40.65=0 | | 85+x+x=180 | | 0.5=x-0.2 | | 184/4 | | 2m-m=17 | | 3*4/15 | | 2sec(x)=0 | | y=480-4x | | 12y^2-28y+15=1 | | 2secx=0 | | P(x)=4x+16 | | sqrt(18x^3/12x) | | 18/9=4 | | 5(1-3n)+7=7(n+8) | | -0.6x+8.49=-0.4x+6.89 | | =b(x+4)+7(x+4) | | 24+x+x=46 | | 4x+55=3x+10 | | 2x+20+x=4x-25 | | 5w+20=4q+16 | | 24+2x=26 | | 1/4(x-6)^2=7 | | 3w+20=4q+16 | | sqrt18x^3/sqrt12x | | b^10/b^2=b^5 | | 2(x-3.7)=3.2 | | 28y=84 | | 15.51x-211.700x+42100000= | | 7-(4x-2)=-294 |

Equations solver categories